AI literacy and academic engagement in higher education: the mediating role of foreign language anxiety - Ashraf Ragab Ibrahim; Mohamed Megahed Nasreldeen; Hesham Hussein Yakout; Hanan Mohamed Elsied; Mohammed Saad Eltawela; Mohamed Ali Nemt-allah (Institute of Advanced Engineering and Science, 2026)
The rapid integration of artificial intelligence (AI) in higher education has raised questions about how technological competencies influence student outcomes, particularly in foreign language learning where anxiety significantly affects performance. This study investigated whether foreign language anxiety (FLA) mediates the relationship between AI literacy (AIL) and academic engagement (AE) among 1,052 English as a foreign language (EFL) learners enrolled in foreign language programs at Al-Azhar University, Egypt. Participants completed three validated instruments: the artificial intelligence literacy scale (AILS), the short-form foreign language classroom anxiety scale (S-FLCAS), and the academic engagement scale (AES). Mediation analysis was conducted using PROCESS Model 4 with 5,000 bootstrap iterations to generate bias-corrected confidence intervals (CI). Correlation analyses revealed that AIL positively correlated with AE (r=.31, p